Tuning the thermoelectrical properties of anthracene-based self-assembled monolayers - Cohen,L (Chemical Science, 2020)
It is known that the electrical conductance of single molecules can be controlled in a deterministic manner by chemically varying their anchor groups to external electrodes. Here, by employing synthetic methodologies to vary the terminal anchor groups around aromatic anthracene cores, and by forming self-assembled monolayers (SAMs) of the resulting molecules, we demonstrate that this method of control can be translated into cross-plane SAM-on-gold molecular films. The cross-plane conductance of SAMs formed from anthracene-based molecules with four different combinations of anchors are measured to differ by a factor of approximately 3 in agreement with theoretical predictions. We also demonstrate that the Seebeck coefficient of such films can be boosted by more than an order of magnitude by an appropriate choice of anchor groups and that both positive and negative Seebeck coefficients can be realised. This demonstration that the thermoelectric properties of SAMs are controlled by their anchor groups represents a critical step towards functional ultra-thin-film devices for future molecular-scale electronics.